Legal Analysis of Default in Credit Agreement (Decision No. 25/Pdt. G. S/2024/PN. Pct.) - Marlina Elisabeth Pakpahan; Elkana Dasilva Ginting; Claudya Yolanda Putri Manalu; Clara Brigitta Jap (Verdict: Journal of Law Science, 2026)
Credit agreements have become one of the principal financing instruments in the Indonesian financial system and hold a strategic position in supporting both consumer and productive sectors. Therefore, credit agreements must comply with Civil Code and Law Number 10 of 1998 concerning Banking to ensure legal certainty and protection for all parties involved. However, in practice, debtors may fail to fulfill repayment obligations, resulting in breach of contract (default). This issue is reflected in Decision Number 25/Pdt.G.S/2024/PN Pacitan, where Bank Rakyat Indonesia Pacitan Branch sued the debtors for non-performance of contractual obligations. This study aims to analyze the regulation of breach of credit agreements, to examine the legal provisions regarding credit agreements, and to analyze the judge’s considerations in deciding Case Number 25/Pdt.G.S/2024/PN Pct. This study applies normative legal research using statutory, conceptual, and case approaches through library research on legal materials. The result showed that breach of contract in judicial practice is interpreted not only as contractual non-compliance but also as civil liability requiring proportional legal remedies, compensation, and judicial balance between creditor protection and debtor rights.